The Changing Nature of Long-Term Care in Maine - Saucier, Paul; Fralich, Julie (Maine Policy Review, 2003)
The increase in the proportion of older adults, many with one or more chronic medical conditions, will increase the demand for long-term care. Paul Saucier and Julie Fralich discuss the socio-demographic factors affecting long-term care policy, and describe various state and federal options for providing and financing long-term care. They note that Maine’s long-term care system has so far been able to absorb considerable growth in people by serving increasing numbers in lower-cost settings. Cost sharing has been introduced, and tax policy has been changed to provide incentives for long-term care insurance. Policymakers must now consider whether the current balance of public and private financing of long-term care is sustainable in the long run.
Keywords: Maine; long-term care; long-term care policy